Effects of nitrogen doping on optical and electrical properties of nanocrystalline FeSi2 films prepared by sputtering - Tomohiro Nogami; Hirokazu Kishimoto; Ryuji Baba; Nathaporn Promros; Tsuyoshi Yoshitake (My University, 2017)
Nitrogen-doped nanocrystalline-FeSi2 (NC-FeSi2) thin films were deposited on SiO2 substrates at room temperature by radio frequency magnetron sputtering, and the effects of nitrogen-doping were experimentally studied. X-ray diffraction measurements revealed that the lattice constant of nano-sized grains increases by nitrogen doping and finally the film becomes amorphous. Optical absorption spectral and electrical measurements indicated that the optical bandgap is evidently enlarged and the electrical conductivity is significantly decreased by nitrogen doping, respectively. It was experimentally demonstrated that nitrogen doping drastically modulate NC-FeSi2 optically and electrically.
Keywords: Nanocrystalline material; Lattice constant; Semiconductor materials and interfaces